Das psychiatrische Gutachten Bernhard von Guddens und die Entmachtung König Ludwigs II. von Bayern 1886: ein Kommentar zum Beitrag von R. Steinberg in Der Nervenarzt 01/2019 = Bernhard von Gudden’s psychiatric assessment and the deposition of King Ludwig II of Bavaria in 1886 : comments on the article by R. Steinberg in Der Nervenarzt 01/2019 - Häfner, Heinz (Der Nervenarzt, 2019)
King Ludwig II of Bavaria drowned himself in Lake Starnberg on 13 June 1886 after subduing and drowning Bernhard von Gudden, a Munich-based psychiatrist who had tried to hold him back. Commissioned by Prince Luitpold, Ludwig’s successor to the throne, von Gudden had provided a psychiatric assessment on the king. Finding him to be suffering from a progressive mental illness and paranoia (madness), he declared Ludwig incapable of ruling. On the basis of this report Ludwig was unlawfully declared incapacitated, deposed, arrested and locked up in the Berg Castle under von Gudden’s medical supervision. We conducted a 5-year psychiatric historical study of King Ludwig II, the most thorough of its kind ever undertaken. The main results were: the private, official and political letters the king wrote until his very last day were reasonable, well-argued and impeccable in style. Until his final days Ludwig had invariably fulfilled his administrative tasks in a prompt and proper way. His handling of political affairs was also wise and reasonable. Due to social phobia afflicting him since his youth he neglected his representative duties as a monarch. Von Gudden’s report is marred by severe flaws. In his article published in Der Nervenarzt (01/2019) R. Steinberg adopts von Gudden’s psychiatric diagnosis and misjudgement. Steinberg writes that the king’s illness developed “in a clear crescendo”. In fact, it was the behavioral anomalies associated with the king’s homosexual relationships that grew increasingly prevalent at the court, whereas Ludwig’s mental efficiency improved over time. Given the historical misjudgment and numerous other errors that Steinberg adopts from von Gudden, I considered it necessary to compare and contrast his conclusions with results from our own research.
Gesehen am 06.12.2019